Regulation of charges over book debts in Nigeria (2017)
There has been considerable debates or whether it is possible to create a fixed charge over book debts and recycling proceeds. The courts have clearly stated that it will go beyond the nomenclature ascribed by the parties to the debenture and ascribe its own interpretation on the debenture, it follows that the intentions of the parties is not useful in the categorisation of charge over book debts. This paper examined the difference between the Fixed charge and the Floating charge, why the creditors will prefer a fixed charge to a floating charge. This paper also examined the nature of Book debts, the problems of categorisation of the charge on Book debts and position of the law in Nigerian law. There is total absence of regulation, categorization and legal framework of Book debts in Nigeria. Though mentioned in the CAMA which perhaps show its recognition, the near absence of regulation has left the position in an unsatisfactory position. This paper calls for a proper regulation of the charge on Book debts in Nigeria. It is important that the proper principles of law must be well understood to enable us determine whether a transaction that is described as fixed or floating charge over Book debts is to all intents and purposes one.